The Development of Fiqh Munākaḥah (Marriage Jurisprudence) Material Course in Madurese Islamic Universities and Its Relation with Gender Equality and Divorce Prevention - Maimun Maimun; Ainul Haq Nawawi; Abdul Haq Syawqi (Al-Ihkam: Jurnal Hukum dan Pranata Sosial, 2020)
Explanation of Law 1/1974, number 4 point e, obviously accentuates the principle of complicating divorce. It requires specific reasons beyond the lawsuit and, in line with article 115 of KHI (Kompilasi Hukum Islam; Islamic Compilation Book), obliges the process to take place in the court trial. This implies that divorce needs prevention from the whole parties both persons and institutions, including Islamic universities. Islamic universities have both academic and social responsibilities to prevent divorce due to their strategic duties and function in community development and empowerment, specifically for spreading knowledge. This research aims to identify how far Madurese Islamic universities perform their roles and function by designing fiqh munākaḥah (marriage jurisprudence) materials for students as prospective husbands and wives. It focuses on whether the materials get developed and are compatible with gender equality and divorce prevention efforts. Using a qualitative approach particularly its phenomenological type, this study took place in three Madurese Islamic universities. It revealed that the latest development of fiqh munākaḥah materials are still mostly about the normative perspective from classical fiqh literature with very little relevances to either gender equality spirit or divorce prevention effort. (Penjelasan UU Nomor I Tahun 1974, angka 4, huruf e, jelas menekankan prinsip untuk mempersukar perceraian dengan mewajibkan alasan-alasan tertentu serta, senada dengan KHI Pasal 115, mengharuskan proses perceraian terjadi di depan sidang pengadilan. Ini menunjukkan bahwa tugas mencegah perceraian harus dilakukan siapapun, baik perorangan ataupun instansi, termasuk Perguruan Tinggi Islam. Perguruan Tinggi Islam memiliki tanggung jawab akademik dan sosial karena tugas dan fungsinya yang strategis dalam pengembangan dan pemberdayaan masyarakat, terutama dalam penyebaran pengetahuan. Untuk mengetahui sejauh mana Perguruan Tinggi Islam di Madura menjalankan peran dan fungsinya tersebut, penelitian ini menelusuri kajian fiqh munākaḥah sebagai bahan konsumsi bagi calon-calon suami dan istri, khususnya apakah materi-materi tersebut sudah berkembang dan sesuai dengan wacana kesetaraan gender dan upaya pencegahan perceraian. Menggunakan pendekatan kualitatif berjenis fenomenologis, penelitian ini mengambil setting di 3 Perguruan Tinggi Islam di Madura. Hasil penelitian menunjukkan bahwa perkembangan terbaru kajian fiqh munākaḥah masih didominasi kajian normatif dari sumber fiqh klasik sehingga belum relevan dengan semangat kesetaraan gender maupun upaya pencegahan perceraian)